Thrombus straddling a patent foramen ovale - Prota, Costantina; Citro, Rodolfo; Silverio, Angelo; Ascoli, Roberto; Naddeo, Corrado; Vitale, Giovanni; Piscione, Federico (Monaldi Archives for Chest Disease, 2015)
We present a case of a 67-year-old male with pulmonary embolism. Transesophageal echocardiography (TEE) showed the presence of a mobile thrombus straddling the patent foramen ovale (PFO) and prolapsing into both atria. Treatment with heparin was started. Five days after admission, repeat TEE revealed a reduction in thrombus dimensions, so anticoagulation therapy was continued. Eleven days after admission, TEE showed complete disappearance of the thrombus.